DEVELOPMENT OF CONTROL AND MONITORING SYSTEM FOR ILLUMINATION OF THE DEPARTMENT OF ELECTRICAL ENGINEERING BASED ON THE INTERNET OF THINGS (IOT) - Muliadi Muliadi; Ruslan Ruslan; Riska Iqbal (Jurusan Pendidikan Teknik Elektro, 2023)
This research is a research and development (R&D) study utilizing the prototype development model. The aim of this study is to produce a development of an internet of things-based lighting control system. The functionality testing results achieved a 100% score, indicating that the prototype is suitable for use, and the user response results obtained a 100% score with the